Human-centered design approach for enhancing supply chain management systems in SMEs: insights from Malaysia - Ahmad, Sabrina; Zainudin, Nurhamizah; Ermahani A. Jalil, Intan; Hefri Ariyanto, Hepy; Ahmad, Mazida (Bulletin of Electrical Engineering and Informatics, 2025)
A reliable supply chain management (SCM) system is crucial to small and medium enterprises (SMEs) to meet the increasing demands of supply chain operations. However, the misalignment between the functional SCM system and the complex, dynamic, and diverse needs of the supply chain stakeholders is paramount. This paper presents an effort to adopt human-centered design (HCD) in the process of identifying requirements for a SCM system, aimed at providing valuable support to SMEs. The HCD places a strong emphasis on shaping design choices in alignment with users' tasks, needs, and preferences, instead of requiring users to adapt their behaviors to fit the system. The survey method is employed to get the SMEs' perspectives on the potential benefits of incorporating HCD into the requirements of the SCM system. The findings showed that a minimum of 80% of the respondents agreed that HCD brings numerous benefits to the development of SCM systems for SMEs in Malaysia.